Apoptosis Methods in Pharmacology and Toxicology Approaches to Measurement and Quantification - Davis, Myrtle A; Ed (Humana Press, 2002)
Apoptosis, or programmed cell death, is a widespread cellular process that regulates numerous important biological events ranging from the metamorphosis of the tadpole tail to the elimination of surplus brain cells in the formation of proper synaptic connections. In Apoptosis Methods in Pharmacology and Toxicology: Approaches to Measurement and Quantification, Dr. Myrtle A. Davis has assembled a panel of cutting-edge scientists to describe their best methods for detecting, illuminating, and quantifying apoptotic mechanisms in a way that is useful in toxicology and pharmacology research. These state-of-the-art techniques include flow cytometric, fluorometric, and laser scanning methods for quantifying and characterizing apoptosis, as well as protocols for the use of DNA microarray technology, high-throughput screens, and ELISA. Immunocytochemical methods for measuring biochemical and molecular endpoints in tissue sections will be highly useful for those carrying out studies in whole animal models as opposed to cell culture systems. Presented by authors well-versed in the technical problems and challenges in analyzing apoptosis, each method explicates its successful use, describes its limitations, and shows how it may be applied in large-scale screening operations. Concise and eminently practical, Apoptosis Methods in Pharmacology and Toxicology: Approaches to Measurement and Quantification offers pharmacologists, toxicologists, pathologists, and many other biomedical scientists today's gold standard reference source for methods that definitively identify and accurately quantify apoptosis.